2021
DOI: 10.1039/d1se01076j
|View full text |Cite
|
Sign up to set email alerts
|

Operation of calcium-birnessite water-oxidation anodes: interactions of the catalyst with phosphate buffer anions

Abstract: Investigating the interfaces between electrolytes and electrocatalysts during electrochemical water oxidation is of great importance for an understanding of the factors influencing catalytic activity and stability. Here, the interaction of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Consequently, the different surface chemistry in the initial state can only explain why the current density of the (010)-oriented film is more than 100% higher than that of the (001)-oriented film if Ca­(OH) 2 plays an important role. Indeed, the role of Ca hydroxide species in the stabilization of active Mn 3+ states was discussed for another layered manganese oxide compound, namely, Ca birnessite . However, the valence states of Mn in both epitaxial orientations are 3.2 (010) and 3.3 (001), respectively, which are very similar and do not connect to the higher hydroxide surface concentration at the (010) films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the different surface chemistry in the initial state can only explain why the current density of the (010)-oriented film is more than 100% higher than that of the (001)-oriented film if Ca­(OH) 2 plays an important role. Indeed, the role of Ca hydroxide species in the stabilization of active Mn 3+ states was discussed for another layered manganese oxide compound, namely, Ca birnessite . However, the valence states of Mn in both epitaxial orientations are 3.2 (010) and 3.3 (001), respectively, which are very similar and do not connect to the higher hydroxide surface concentration at the (010) films.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the role of Ca hydroxide species in the stabilization of active Mn 3+ states was discussed for another layered manganese oxide compound, namely, Ca birnessite. 30 However, the valence states of Mn in both epitaxial orientations are 3.2 (010) and 3.3 (001), respectively, which are very similar and do not connect to the higher hydroxide surface concentration at the (010) films.…”
Section: Ruddlesden−popper Pcmo Epitaxialmentioning
confidence: 96%
“…The involvement of lattice oxygen is strongly linked to the electronic structure of the catalyst ,, and in particular to the appearance of electron holes on lattice oxygen atoms, occurring in the presence of high M-O covalency resulting either from orbital overlap or from a negative charge transfer regime. It is not clear, however, whether the involvement of lattice oxygen is linked to the catalyst instability, , or whether the high covalency of the M-O bond could result in reduced dissolution and increases stability. , …”
Section: Discussionmentioning
confidence: 99%
“…The characterization of phosphorus species has been carried out in natural and synthetic materials using a variety of methods [6][7][8][9][10]28,[35][36][37][38], featuring, e.g., infrared and Raman spectroscopy [39,40], neutron scattering [41], 31 P nuclear magnetic resonance spectroscopy [10,[42][43][44], and X-ray spectroscopy techniques [9,36,[45][46][47][48][49][50]. For the CoCat, the properties of the P species were studied by various approaches [6][7][8][9][10]18,35].…”
Section: Introductionmentioning
confidence: 99%
“…In electrodeposited amorphous CoCat films, phosphorus was found to be present as orthophosphate (PO 4 3− ) [7]. In related Ca-birnessite MnO X structures, P-rich surface layers were observed, and two possible P binding modes were suggested, with phosphate either directly bound to O-vacancies in the [ MnO 6 ] layers or phosphate associated with Ca 2+ in the interlayer space forming Ca/PO 4 /H 2 O complexes [38]. Replacing phosphorus with arsenic in the CoCat facilitated (technically easier) XAS studies at the As K-edge [28] and revealed two possible binding motifs, with arsenate either bridging two Co centers at the margins of the CoCat layers or substituting cobalt ions within the oxide layers.…”
Section: Introductionmentioning
confidence: 99%